Restorasi Agribisnis Kakao di Kecamatan Lilirilau Kabupaten Soppeng dari Aspek Sosial, Ekonomi dan Kelembagaan Petani - Rhamadani, Naurha; Darma, Rahim; Arsal, Ariady (Jurnal Galung Tropika, 2023)
This research aims to analyze the social, economic and institutional aspects of farmers contributing to the restoration of cocoa agribusiness in Lilirilau District. Apart from that, this research also aims to determine the effect of cocoa agribusiness restoration on increasing the productivity of cocoa farming in Lilirilau District, Soppeng Regency, South Sulawesi. Research uses quantitative and qualitative approaches. The quantitative analysis used in this research is SEM analysis with Smart PLS 4.0, while the qualitative analysis uses qualitative descriptive data analysis. The influence of the social aspect obtained a path coefficient of (t = 0.415, p = 0.679 > 0.05) which means it does not have a positive and significant influence on the restoration of cocoa agribusiness. Then, the economic aspect obtained a path coefficient of (t = 6.334, p = 0.000 < 0 .05) which means that it has a positive and significant influence on the restoration of cocoa agribusiness as well as institutional aspects. The path coefficients obtained are (t = 0.431, p = 0.667 > 0.05) which means that it does not have a positive and significant influence on the restoration of cocoa agribusiness and agribusiness restoration is obtained. path coefficients of (t = 7.333, p = 0.000 > 0.05) which means it has a positive and significant influence on increasing the productivity of cocoa farming in Lilirilau District, Soppeng Regency.